Investigating the antecedents and outcomes of work-life balance: evidence from garment industries in Indonesia - Sari Wahyuni; Dian Rahmasari (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The garment industry is one of the main contributors to Indonesia's GDP. However, work-life balance has become a crucial issue for workers in this industry. This study aims to investigate the antecedents and outcomes of work-life balance among workers in the garment industry. More specifically, we examine the effect of asset ownership and working conditions (health conditions, compensation, and working hours) affect work-life balance. Furthermore, we also examine the effect of work-life balance on job satisfaction, life satisfaction, and turnover intention. We collected data using a survey of 3691 garment workers in Central Java, West Java, DI Yogyakarta, DKI Jakarta, and Banten. The analysis shows that work-life balance could increase workers' life satisfaction and job satisfaction. Interestingly, health condition is found out to be the important variable that could improve work-life balance significantly.